Inflammation‐induced sensitization of the brain in term infants. (April 2015) - Fleiss, Bobbi; Tann, Cally J; Degos, Vincent; Sigaut, Stéphanie; Van Steenwinckel, Juliette; Schang, Anne‐Laure; Kichev, Anton; Robertson, Nicola J; Mallard, Carina; Hagberg, Henrik; Gressens, Pierre
Abstract : Perinatal insults are a leading cause of infant mortality and amongst survivors are frequently associated with neurocognitive impairment, cerebral palsy (CP), and seizure disorders. The events leading to perinatal brain injury are multifactorial. This review describes how one subinjurious factor affecting the brain sensitizes it to a second injurious factor, causing an exacerbated injurious cascade. We will review the clinical and experimental evidence, including observations of high rates of maternal and fetal infections in term‐born infants with neonatal encephalopathy and cerebral palsy. In addition, we will discuss preclinical evidence for the sensitizing effects of inflammation on injuries, such as hypoxia–ischaemia, our current understanding of the mechanisms underpinning the sensitization process, and the possibility for neuroprotection.